The motivation of bloggers for organisational knowledge sharing and creation: A comparative case study to identify contingency factors influencing motivation. (3rd December 2009) - Kaiser, Stephan; Kansy, Simone; Mueller-Seitz, Gordon; Ringlstetter, Max
The use of weblogs for knowledge sharing and creation is a novel social and organisational phenomenon. In this paper, we start from the assumption that successful knowledge management requires the motivation of people to engage in knowledge-related communication. However, several studies indicate that Information and Communication Technologies (ICTs) do not always improve organisational knowledge sharing and creation as a result of a missing motivation to use ICTs. Thus, we discuss two partially opposite cases, in order to identify and explain contingency factors that directly influence the motivation towards making a contribution in knowledge sharing and creation.